MicroRNA-194-5p Attenuates Doxorubicin-Induced Cardiomyocyte Apoptosis and Endoplasmic Reticulum Stress by Targeting P21-Activated Kinase 2 - Fa, Hongge; Xiao, Dandan; Chang, Wenguang; Ding, Lin; Yang, Lanting; Wang, Yu; Wang, Mengyu; Wang, Jianxun (Frontiers in Cardiovascular Medicine, 2022)
Objective: Many studies reported that microRNAs (miR) are involved in the regulation of doxorubicin (DOX)-induced cardiotoxicity. MiR-194-5p has been reported significantly up-regulated in myocardial infarction patients, however, its role in myocardial diseases is unclear. Various stimuluses can trigger the endoplasmic reticulum (ER) stress, and it may activate the apoptosis signals eventually. This study aims to explore the regulatory role of miR-194-5p in DOX-induced endoplasmic reticulum stress and cardiomyocyte apoptosis. Methods: H9c2 was treated with 2μM DOX to induce apoptosis, which is to stimulate the DOX-induced cardiotoxicity model. The expression of miR-194-5p was detected by real-time quantitative polymerase chain reaction (RT-qPCR); the interaction between miR-194-5p and P21 activated kinase 2 (PAK2) was tested by dual luciferase reporter assay; TUNEL (terminal deoxinucleotidyl transferase-mediated dUTP-fluorescein nick-end Labeling) assay and caspase 3/7 activity were used to assess apoptosis; trypan blue staining was applied to measure cell death; western blotting was performed to detect protein expressions; and endoplasmic reticulum-related factors XBP1s (splicing X-box binding protein 1) was detected by polyacrylamide gel electrophoresis and immunofluorescence, to verify the activation of endoplasmic reticulum stress. Results: MiR-194-5p was up-regulated in cardiomyocytes and mouse heart tissue with DOX treatment, while the protein level of PAK2 was down-regulated. PAK2 was predicted as the target of miR-194-5p, hence, dual luciferase reporter assay indicated that miR-194-5p directly interacted with PAK2 and inhibited its expression. TUNEL assay, caspase-3/7 activity test and trypan blue stain results showed that either inhibition of miR-194-5p or overexpression of PAK2 reduced DOX-induced cardiomyocyte apoptosis. Silencing of miR-194-5p also improved DOX-induced cardiac dysfunction. Additionally, DOX could induce endoplasmic reticulum stress in H9c2, which led to XBP1 and caspase-12 activation. The expression of XBP1s under DOX treatment increased first then decreased. Overexpression of XBP1s suppressed DOX-induced caspase-3/7 activity elevation, as well as the expression of cleaved caspase-12, which protected cardiomyocyte from apoptosis. Additionally, the activation of XBP1s was regulated by miR-194-5p and PAK2. Conclusion: Our findings revealed that silencing miR-194-5p could alleviate DOX-induced cardiotoxicity via PAK2 and XBP1s in vitro and in vivo. Thus, the novel miR-194-5p/PAK2/XBP1s axis might be the potential prevention/treatment targets for cancer patients receiving DOX treatment.